The mediating role of social goals in the relationships between teachers’ transformational leadership, prosocial climate, and motor self-efficacy in physical education students - Reigal-Garrido, Rafael Enrique; Morales-Sánchez, Verónica Odilia; Matos, Rui; Hernández-Mendo, Antonio (Frontiers, 2025)
Background: There is a limited body of research explaining the associations between transformational leadership and prosocial climate, particularly when considering social goals as mediating variables. Furthermore, no studies have explored the mediating effect of social goals and prosocial climate in the relationships between transformational leadership and motor self-efficacy. Purpose: The aim of this study was to examine the relationships between transformational leadership, social goals, prosocial climate, and the perception of motor self-efficacy. Specifically, this research intends to determine the mediating role of social goals in the relationships between teacher transformational leadership, prosocial climate, and motor self-efficacy in Physical Education students. Method: The study involved 392 adolescents (52.81% male, n = 207; 47.19% female, n = 185) aged between 14 and 16 years (M = 15.07; SD = 0.78), who were secondary school students in various educational institutions in the city of Málaga (Spain). Data were collected using the Transformational Teaching Questionnaire, the Social Goals in Physical Education Scale, the School Prosocial Climate Questionnaire, and the Motor Self-Efficacy Scale. Results: The results revealed multiple relationships among the studied variables. Specifically, a mediation effect of social goals was observed between transformational leadership and prosocial climate, as well as a mediation effect of social goals and prosocial climate in the relationship between transformational leadership and motor self-efficacy. Conclusion: These findings suggest an association between transformational leadership, prosocial climate, and motor self-efficacy, highlighting the importance of social goals as key variables in understanding these relationships.
Este artículo de Frontiers in Psychology examina cómo se relacionan el liderazgo transformacional de los profesores, las metas sociales de los estudiantes, el clima prosocial en la clase y la percepción de autoeficacia motora en alumnos de Educación Física, con el objetivo de determinar si las metas sociales median estas relaciones. Para ello, se estudió a 392 adolescentes españoles de 14 a 16 años, evaluando mediante cuestionarios validados la percepción del estilo de enseñanza transformacional del docente, las metas sociales en EF, el clima prosocial percibido y la autoeficacia motora. Los resultados mostraron que las metas sociales ejercen un efecto mediador significativo entre el liderazgo transformacional y el clima prosocial, y que tanto las metas sociales como el clima prosocial median en la relación entre el liderazgo transformacional y la autoeficacia motora, sugiriendo que un profesor con estilo transformacional puede fomentar metas sociales en sus alumnos que, a su vez, contribuyen a un clima de clase más prosocial y a una mayor percepción de competencia motora. Estos hallazgos resaltan la importancia de promover metas sociales a través de un liderazgo docente inspirador para mejorar el entorno social y la autoconfianza en tareas motrices en clases de Educación Física.
Keywords: Educación física; Profesores de educación física; Liderazgo en la enseñanza; Physical education; Transformational leadership; Prosocial; Social goals; Motor self-efficacy